Gait training facilitates central drive to ankle dorsiflexors in children with cerebral palsy - Willerslev-Olsen, Maria (Brain, 2015)
Foot drop and toe walking are frequent concerns in children with cerebral palsy. The main underlying cause of these problems is early damage and lack of maturation of the corticospinal tract. In the present study we investigated whether 4 weeks of daily treadmill training with an incline may facilitate corticospinal transmission and improve the control of the ankle joint in children with cerebral palsy. Sixteen children with cerebral palsy (Gross Motor Classification System I:6, II:6, III:4) aged 5–14 years old, were recruited for the study. Evaluation of gait ability and intramuscular coherence was made twice before and twice after training with an interval of 1 month. Gait kinematics were recorded by 3D video analysis during treadmill walking with a velocity chosen by the child at the first evaluation. Foot pressure was measured by force sensitive foot soles during treadmill and over ground walking. EMG-EMG coherence was calculated from two separate electrode recordings placed over the tibialis anterior muscle. Training involved 30 min of walking daily on a treadmill with an incline for 30 days. Gait training was accompanied by significant increases in gait speed, incline on the treadmill, the maximal voluntary dorsiflexion torque, the number and amplitude of toe lifts late in the swing phase during gait and the weight exerted on the heel during the early stance phase of the gait cycle. EMG-EMG coherence in the beta and gamma frequency bands recorded from tibialis anterior muscle increased significantly when compared to coherence before training. The largest changes in coherence with training were observed for children <10 years of age. Importantly, in contrast to training-induced EMG increases, the increase in coherence was maintained at the follow-up measurement 1 month after training. Changes in the strength of coherence in the beta and gamma band were positively correlated with improvements in the subjects’ ability to lift the toes in the swing phase. These data show that daily intensive gait training increases beta and gamma oscillatory drive to ankle dorsiflexor motor neurons and that it improves toe lift and heel strike in children with cerebral palsy. We propose that intensive gait training may produce plastic changes in the corticospinal tract, which are responsible for improvements in gait function.